Implementation of Canva Application-Based Assure Model Learning Design in Fiqh Learning - Sari, Desi Mulia; Hasanah, Mila (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this essay is to achieve a design for education that is in line with effective and efficient standards. The development of information technology requires teachers to be able to use it as much as possible to support learning. This writing uses a qualitative descriptive method, by describing the ASSURE model design based on the Canva application. The results showed that the use of the ASSURE model based on the Canva application added variety to learning and increased student learning motivation, by analyzing student characteristics, and learning styles, choosing appropriate methods, media, and teaching materials, and involving students actively in learning. In addition, the use of the Canva application-based ASSURE model learning design increases the value drastically in the evaluation of Fiqh learning. The ASSURE model learning design in a nutshell is the process of designing a learning model from analyzing the character of students, how to learn, choosing and applying methods, appropriate learning media, and conducting evaluations and revisions during learning. In designing Canva application-based learning, it is necessary to adjust to student interests and the times, so that the learning process is not boring and more interesting.